2021
DOI: 10.1002/fsh.10584
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence for Depensation in Freshwater Fisheries

Abstract: Inland fisheries face increasing threats to their sustainability. Despite speculation that depensation may exacerbate the effects of stressors on population resiliency, depensation has not been empirically explored in freshwater fisheries. Declining productivity of Walleye Sander vitreus populations in northern Wisconsin foreshadows an underlying change in naturally reproduced juvenile Walleye survival. We used long‐term stock and recruitment data from lakes in the Ceded Territory of Wisconsin to quantify dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 45 publications
4
60
0
Order By: Relevance
“…For Sherman Lake, compensatory age-0 to age-1 survival and a significant decline in length at maturity appears to have resulted in a relatively stable adult stock size with correspondingly low and variable age-0 recruitment. Sherman Lake exhibits strong resilience to exploitation in its stock-recruitment relationship and does not show strong support for depensatory recruitment dynamics (Tsehaye et al 2016;Sass et al 2021). Clearly, the weak adult abundance response to elevated exploitation did not negatively influence recruitment by reducing stock size below a critical depensatory threshold, which has also been observed in other Walleye exploitation studies .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…For Sherman Lake, compensatory age-0 to age-1 survival and a significant decline in length at maturity appears to have resulted in a relatively stable adult stock size with correspondingly low and variable age-0 recruitment. Sherman Lake exhibits strong resilience to exploitation in its stock-recruitment relationship and does not show strong support for depensatory recruitment dynamics (Tsehaye et al 2016;Sass et al 2021). Clearly, the weak adult abundance response to elevated exploitation did not negatively influence recruitment by reducing stock size below a critical depensatory threshold, which has also been observed in other Walleye exploitation studies .…”
Section: Discussionmentioning
confidence: 63%
“…For example, 10 years of 35% annual exploitation on Big Crooked Lake, Wisconsin, significantly reduced the total adult Walleye density from about WALLEYE RESPONSES TO ELEVATED EXPLOITATION 541 16 to 10 fish/ha, with total adult density being reduced to about 7 fish/ha during the later stages of the study . According to Tsehaye et al (2016) and Sass et al (2021), Sherman Lake and Big Crooked Lake were highly resilient to elevated-exploitation rates given their strong, compensatory stock-recruitment relationships and lack of depensatory recruitment dynamics. Nevertheless, other Walleye populations in the CTWI may not be as resilient to elevated exploitation and many show depensatory recruitment dynamics (Rypel et al 2015(Rypel et al , 2018Embke et al 2019;Sass et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is possible that Walleye were headed toward extinction due to recruitment failures that occurred at low SSB in at least some lakes (i.e., depensatory stock-recruitment; Walters and Kitchell 2001;Sass et al 2021), assessments showed that many of these populations were "rescued" by strong recruitment events that occurred in the late 1990s to early 2000s and before SSB could have recovered following fishing mortality reductions in 1996. This finding raises the important possibility that at least some Walleye populations have always been sustained by occasional episodic recruitment events, and persisted under high fishing pressure because favorable recruitment events occurred even though population age structures and egg production were severely impacted by high fishing rates (see Sullivan 2003;Sullivan 2004;this study).…”
Section: R a F Tmentioning
confidence: 99%
“…Second, depensatory decreases in per capita recruitment at low abundance can lock a population into a cycle of decline once abundance has been reduced below a critical threshold. Density‐dependent Allee effects or cultivation–depensation food web dynamics can cause these depensatory responses (Kramer et al., 2009; Sass et al., 2021; Walters & Kitchell, 2001).…”
Section: Introductionmentioning
confidence: 99%